Calibration of the limiting current of oxygen sensors by the Fermi–Dirac distribution. (3rd March 2015) - Changshi, Liu; Feng, Li
Abstract: Based on Fermi–Dirac distribution, a physical model describing the current–voltage characteristics of limiting ‐current oxygen sensors is presented. The model focuses on the prediction of the current via voltage by using an analytically invertible method. T he response of oxygen concentration to limiting current is explained theoretically via a function. The simulations agree very well with the observed curves (either current versus voltage or oxygen concentration versus limiting current). Consequently, the oxygen concentration can be predicted from limiting current by using only one function. Copyright © 2015 John Wiley & Sons, Ltd.